Trial data on the antenna and reference panels for 10 locations is available on the project's website - CGIAR Research Program on Rice (2019)
Phenotyping and weather data from 10 locations available at project site. Other data sets are being validated and curated for loading. Initial analyses for adjustment of trials by experimental design accomplished.